COVID-19 & the Opioid Crisis: Harm & Harm Reduction at the Intersection - Ricci, Melissa (My University, 2021)
This project utilized an interdisciplinary approach to explore what harm and harm reduction meant during intersecting public health emergencies, the opioid crisis and the coronavirus pandemic. Using thematic and historical analysis, I analyzed interviews with frontline workers, news coverage, and municipal government documents to understand how people conceptualized the opioid crisis during coronavirus (and vice versa). On the whole, I found that harm reduction was a central aspect of the efforts against the opioid crisis in Hamilton. However, there were discrepancies in how it was practiced and understood. Generally, harm reduction was presented in municipal government documents as a medical intervention that involved, for example, the provision of new needles and naloxone kits to prevent disease and death. Such a practice was indeed important to address the unique harms at the intersection of COVID and the opioid crisis. However, to frontline workers and activists, harm reduction was a much broader term: it included services that were crucial to daily life, such as food and washrooms; the right to safe housing; and broader social and structural interventions, such as the decriminalization of opioid use. The context of the coronavirus pandemic, which exposed people who use opioids to unique harms, exacerbated the disparity between these definitions: harm reduction was simultaneously presented as a narrow, medical practice and a broad, political intervention.
Keywords: covid-19; harm reduction; opioid crisis; Hamilton, ontario; social history; health studies; homelessness; pandemic; encampments; coronavirus; nursing; frontline workers